Morphology of Extreme and Far Ultraviolet Martian Airglow Emissions Observed by the EMUS Instrument on Board the Emirates Mars Mission. Issue 19 (30th September 2022) - Jain, Sonal K.; Deighan, Justin; Chaffin, Mike; Holsclaw, Greg; Lillis, Rob; Fillingim, Matt; Evans, J. Scott; Correira, John; AlMatroushi, Hessa; Lootah, Fatma; England, Scott; AlMazmi, Hoor; et al.
Abstract: We present the first continuous observations of the extreme and far ultraviolet (EUV and FUV) dayglow emissions measured by Emirates Mars Ultraviolet Spectrometer (EMUS) onboard the Emirates Mars Mission. We found excellent agreement between the previous observations from the Hopkins Ultraviolet Telescope and recent observations by EMUS both in shape and magnitude. We presented the average disk brightness of major EUV and FUV emissions for about 10 months of data from April 2021 to February 2022. The solar activity was mild/minimum during the first half of the period presented in this study, but we noticed significant day‐to‐day variations in the major dayglow emissions independent of solar activity, indicating possible coupling from the lower atmosphere via waves/tides. The solar activity increased significantly during the second half of the study period. Our analysis showed that all major EUV and FUV emissions are highly correlated with solar forcing as well as seasonal changes. Plain Language Summary: Emirates Mars Ultraviolet Spectrograph on the Emirates Mars Mission is capable of observing emissions emanating from Mars' upper atmosphere in Extreme and Far Ultraviolet wavelengths. This is the first orbital mission to Mars that can observe Mars in extreme ultraviolet (EUV) wavelengths that provide important information about minor atmospheric species on Mars. Our analysis in this study shows that both EUV and far ultraviolet disk emissions on Mars show large day‐to‐day variability in short term. These emissions show long‐term variability that depends on the season and solar forcing. Key Points: First continuous observations of extreme ultraviolet (EUV) and far ultraviolet (FUV) dayglow on Mars Most of the EUV and FUV emissions observations show variations related to season and solar forcing Emirates Mars ultraviolet spectrograph observations are in agreement with the Hopkins ultraviolet telescope observations during solar minimum